Immunological and Neurological Signatures of the Co-Infection of HIV and HTLV: Current Insights and Future Perspectives - Md. Nazmul Islam; Masuma Akter Mili; Israt Jahan; Cotton Chakma; Rina Munalisa (Viruses)
The human retroviruses HIV and HTLV-1/HTLV-2 are transmitted through similar pathways but result in markedly different diseases. This review delineates the immune-mediated mechanisms by which HTLVs influence HIV pathology in co-infected individuals. In the context of HIV co-infection, HTLV-1/HTLV-2 alter the cellular microenvironment to enhance their own survival while simultaneously impeding the progression of HIV. Despite the extensive body of literature on the biological and clinical implications of retroviral co-infections, decades of research have been marred by controversy due to several flawed epidemiological studies and anecdotal reports lacking robust statistical and scientific backing. Nevertheless, recent systematic and well-designed research has led to a growing consensus supporting at least three key conclusions: (1) co-infections of HIV-1 and HTLV-1 are frequently observed in patients with elevated CD4+ T-cell counts who present with lymphoma or neurological complications; (2) HIV-1 and HTLV-2 co-infections have been associated in some instances with a “long-term non-progressor” phenotype; (3) the differential function and/or overexpression of the HTLV-1 and HTLV-2 Tax proteins are likely crucial in the clinical and immunologic outcomes of HIV/HTLV-1 and -2 co-infections. The present review will provide a comprehensive account of research on retroviral co-infections, focusing particularly on their clinical manifestations and associated pathological features.